Storage proteins in accessions of a rice core collection - Silveira, Ricardo Diógenes Dias; Santos, Karina Freire d' Eça Nogueira; Didonet, Claudia Cristina Garcia Martim; Didonet, Agostinho Dirceu; Brondani, Claudio (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to quantify the total storage protein content of 550 accessions from Coleção Nuclear de Arroz da Embrapa (Embrapa Rice Core Collection – CNAE), and to evaluate the SDS-PAGE profile of the 20 accessions that showed the highest storage protein content. High storage protein content was found in 103 CNAE accessions (≥12.0%), intermediate content (11.9 to 9.0%) in 309, and low protein content (≤ 8.9%) in 138. Six out of the 20 accessions with the highest storage protein content showed a differential profile for glutelin, which is the most abundant rice storage protein fraction. There is a large variability of rice storage protein in CNAE accessions, which can be explored in breeding programs to increase the nutritional value of the rice consumed in Brazil.